A review of the genus Ditylometopa Kertész (Diptera: Stratiomyidae) - Woodley, Norman E. (Zootaxa, 2009)
The genus Ditylometopa Kertész (Diptera: Stratiomyidae, Clitellariinae), which occurs only in the Neotropical Region, is reviewed. Euryneura rufifrons Curran, 1934 is synonymized with Ditylometopa elegans Kertész, 1923. A neotype is designated for D. elegans. Two species are recognized, including Ditylometopa centralensis sp. nov., which is described from Costa Rica (type locality) and Nicaragua and may occur in Brazil.